POLYMORPHISM OF THE TP53 GENE IN PATIENTS WITH GASTRIC CANCER IN PROSPECTIVE AND CLINICAL CASE-CONTROL STUDIES - A. V. Belkovets; S. A. Kurilovich; V. N. Maksimov; Yu. I. Ragino; L. V. Scherbakova; O. V. Cheremisina; N. V. Cherdyntseva; M. V. Parulikova; M. I. Voevoda (Сибирский онкологический журнал, 2018)
Background. A functionally significant TP53Arg72Pro polymorphism can contribute to the development of gastric cancer (GC).The aim: to study the associations of genotypes and alleles of the TP53Arg72Pro 4 polymorphism with GC and biomarkers of gastric ucosal atrophy in population-based prospective and case-control clinical trials among the population of Siberia.Material and methods. As a part of the epidemiological study, data of the international multicenter HAPIEE project for 2003–05, based on a population sample of residents of Novosibirsk city (serum and  DNA samples) and data of the population-based registry of GC  (2012) were compared. Gastric cancer patients were matched by  age and sex to HAPIEE population controls. A total of 156 serum  samples (GC – 52, control – 104) and 146 DNA samples (GC – 50,  control – 96) were available for prospective analysis. DNA samples  from 80 gastric cancer patients (45 men and 35 women, mean age  61.0 ± 13.4 years) and from 87 age-and sex-matched controls were  analyzed. DNA samples from venous blood were genotyped  according to standard methods. Serum samples were tested using  diagnostic kit for enzyme-linked immunosorbent assays to determine the levels of pepsinogen I (PGI), PGII, PGI/PGII ratio, gastrin-17 and IgG antibodies to H. pylori.Results. No differences in genotype and allele frequencies of the TP53 gene between the case group and the control group were  found. A decreased frequency of the Pro allele in female gastric  cancer patients compared with controls indicated that the Pro allele  is protective against the development of gastric cancer, but this  effect was not observed in male patients. No associations of TP53  genotypes with the risk of diffuse or intestinal gastric cancer, as well  as with the age and sex of patients were found. A high frequency of  genotypes with the Pro allele in patients with stage III–IV gastric  cancer indicated the relationship between Arg/Pro TR53 and tumor  progression, in particular, the contribution of the minor Pro allele to  the unfavorable prognosis. A prospective study showed high risk of  reducing the level of pepsinogen for assessing predisposition to  gastric cancer.Conclusion. Two case-control studies (population and clinical) conducted in the Western Siberia found no relationship between the  TP53Arg72Pro polymorphism and the risk of gastric cancer. However, the TP53 genotype with a rare Pro allele was associated with atrophic gastritis and severity of gastric cancer.